2005
DOI: 10.1593/neo.05277
|View full text |Cite
|
Sign up to set email alerts
|

EphA2 as a Glioma-Associated Antigen: A Novel Target for Glioma Vaccines

Abstract: EphA2 is a receptor tyrosine kinase and is frequently overexpressed in a wide array of advanced cancers. We demonstrate in the current study that the EphA2 protein is restrictedly expressed in primary glioblastoma multiforme and anaplastic astrocytoma tissues in comparison to normal brain tissues. To evaluate the possibility of targeting EphA2 in glioma vaccine strategies, we stimulated human leukocyte antigen (HLA) A2+ peripheral blood mononuclear cells (PBMCs) obtained from healthy donors and glioma patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
112
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(122 citation statements)
references
References 14 publications
8
112
2
Order By: Relevance
“…We have previously reported that EphA2 883-891 can elicit an HLA-A2-restricted CTL response against glioma cell lines [20]. In addition, recent studies from us [20] and others [32] have revealed that a majority of adult malignant gliomas express high levels of EphA2. More recently, EphA2 mRNA overexpression was found to correlate inversely with survival in a panel of 21 adult GBM cases, and ligand-mediated EphA2 receptor activation increased GBM cell proliferation via a mitogen-activated protein kinase-dependent pathway [33].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…We have previously reported that EphA2 883-891 can elicit an HLA-A2-restricted CTL response against glioma cell lines [20]. In addition, recent studies from us [20] and others [32] have revealed that a majority of adult malignant gliomas express high levels of EphA2. More recently, EphA2 mRNA overexpression was found to correlate inversely with survival in a panel of 21 adult GBM cases, and ligand-mediated EphA2 receptor activation increased GBM cell proliferation via a mitogen-activated protein kinase-dependent pathway [33].…”
Section: Discussionmentioning
confidence: 94%
“…We chose to evaluate these three antigens because they are expressed in adult gliomas and are known to contain CTL epitopes, especially in the context of HLA-A2 [18,20,23]. Our results suggest that EphA2, IL-13α2 and Survivin are suitable targets for developing vaccine strategies for pediatric glioma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, ephrinA binding seems to regulate EphA2 subcellular localization and interaction with other downstream signaling proteins including FAK and the MAP/ERK signaling pathways [8,9]. EphA2 is overexpressed in a variety of human cancers, and high levels of EphA2 are associated with aggressive disease and poor clinical outcomes [10][11][12][13][14][15][16][17][18][19]. In vitro studies have shown that EphA2 is a powerful oncoprotein, sufficient to confer malignant potential on non-transformed epithelial cells [7].…”
Section: Introductionmentioning
confidence: 99%